A comparative study of sperm-egg interactions in birds. - Birkhead, T; Sheldon, B; Fletcher, F (1994)
A comparative study was made of the number of spermatozoa trapped on the outer perivitelline layer and the number of spermatozoa penetrating the inner perivitelline layer of the eggs of 27 species of bird. The total number of spermatozoa (trapped spermatozoa plus holes made by spermatozoa) varied between 29 and 164,000 per egg among species and was significantly and positively correlated with size of the ovum. In most species, holes formed a 'halo' around the germinal disc area and the density of holes was much greater in this region than elsewhere, especially in passerine birds. In some species, a high proportion of holes occurred at some distance from the germinal disc. This seems to be an artefact due to the fact that some spermatozoa trapped in the outer perivitelline layer undergo proteolytic activity between fertilization and oviposition and create additional holes in the inner perivitelline layer both at and away from the germinal disc. Across all species and within most individual species, the number of trapped spermatozoa was positively correlated with the number of holes in the inner perivitelline layer. Decreases in the total number of spermatozoa on successive eggs of a clutch provided an index of the rate at which spermatozoa were used from the sperm storage tubules.